The Simultaneous Effects of miR-145-5p and hsa-let-7a-3p on Colorectal Tumorigenesis: In Vitro Evidence - Nazila Mozammel; Elham Baghbani; Mohammad Amini; Sheyda Jodeiry Zaer; Yalda Baghay Esfandyari; Maryam Tohidast; Seyed Samad Hosseini; Seyed Ali Rahmani; Ahad Mokhtarzadeh; Behzad Baradaran (Tabriz University of Medical Sciences, 2024)
Purpose: MicroRNAs (miRNAs) are a group of small regulatory non-coding RNAs, which are dysregulated through tumor progression. let-7 and MIR-145 are both tumor suppressor microRNAs that are downregulated in a wide array of cancers including colorectal cancer (CRC). Methods: This study was aimed to investigate the effect of simultaneous replacement of these two tumor suppressor miRNAs on proliferation, apoptosis, and migration of CRC cells. HCT-116 with lower expression levels of hsa-let-7a-3p and MIR-145-5p was selected for functional investigations. The cells were cultured and transfected with hsa-let-7a and MIR-145, separately and in combination. Cell viability and apoptosis rates were assessed by MTT assay and flow cytometry, respectively. Cell cycle status was further evaluated using flow cytometry and qRT-PCR was employed to evaluate gene expression. Results: The obtained results showed that exogenous overexpression of MIR-145 and hsa-let-7a in HCT-116 cells could cooperatively decrease CRC cell proliferation and induce sub-G1 cell cycle arrest. Moreover, hsa-let-7a and MIR-145 co-transfection significantly increased apoptosis induction compared to separate transfected cells and control through modulating the expression levels of apoptosis-related genes including Bax, Bcl-2, P53, Caspase-3, Caspase-8, and Caspase-9. Furthermore, qRT-PCR results illustrated that hsa-let-7a and MIR-145 combination more effectively downregulated MMP-9 and MMP-2 expression, as the important modulators of metastasis, compared to the controls. Conclusion: Taken together, considering that exogenous overexpression of MIR-145 and hsa-let-7a showed cooperative anti-cancer effects on CRC cells, their combination may be considered as a novel therapeutic strategy for the treatment of CRC.